2014
DOI: 10.1089/scd.2014.0123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reduced-Intensity and Myeloablative Conditioning Regimens for Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Acute Myeloid Leukemia and Acute Lymphoblastic Leukemia: A Meta-Analysis

Abstract: Currently, the indications to perform reduced-intensity conditioning allogeneic hematopoietic stem cell transplant (RIC-HCT) are based on data derived mainly from large registry and single-centre retrospective studies. Thus, at the present time, there is limited direct evidence supporting the current practice in selecting patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) for RIC versus myeloablative conditioning (MAC) transplants. To determine the relationship between dose inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 59 publications
(80 reference statements)
4
22
1
1
Order By: Relevance
“…In addition, the GRFS, which is a surrogate for quality of life analysis, was similar between the two regimens. Several retrospective analyses and meta-analyses supported these observations [49]. Luger et al reported in the largest such comparison from CIBMTR, including 3731 MAC and 1448 RIC/nonmyeloablative (NMA) recipients, that the 5-year OS rates were 34, 33, and 26 % after MAC, RIC, and NMA conditioning, respectively [5].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the GRFS, which is a surrogate for quality of life analysis, was similar between the two regimens. Several retrospective analyses and meta-analyses supported these observations [49]. Luger et al reported in the largest such comparison from CIBMTR, including 3731 MAC and 1448 RIC/nonmyeloablative (NMA) recipients, that the 5-year OS rates were 34, 33, and 26 % after MAC, RIC, and NMA conditioning, respectively [5].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown similar survival of AML patients after SCT with RIC or MAC [39]. Most of these studies have shown that RIC is associated with reduced non-relapse mortality (NRM) but increased relapse rate, resulting in a similar leukemia-free survival (LFS) as MAC.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, RIC regimens have allowed successful transplantation of patients who are heavily pretreated, older or have complicating comorbidities. (1-5) Fludarabine phosphate is an antitumor and immunosuppressive agent, and is a critical component of most RIC regimens in combination with other chemotherapeutics and/or total body irradiation (TBI).…”
Section: Introductionmentioning
confidence: 99%
“…Either myeloablative conditioning (MAC) or reduced-intensity conditioning (RIC) regimens were used before alloSCT. A meta-analysis published by Wahid et al [46] showed that there was no OS benefit with MAC over RIC regimens. However, for autoSCT, several reports showed that a high-dose cytarabine-containing regimen provided a favorable long-term RFS of 61–71% [35, 47].…”
Section: Discussionmentioning
confidence: 99%